Literasi Mikroskop Mahasiswa Pendidikan Biologi : Pelatihan Penggunaan Mikroskop untuk Meningkatkan Pengetahuan dan Keterampilan - Mursali, Saidil; Sumarjan, Sumarjan; Primawati, Sri Nopita; Nurhidayati, Siti; Firdaus, Laras; Arifin, Ahmad Aris; Sapina, Saifudin; Dewi, Vera Puspita (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
Department of Biology Education, Mandalika University of Education plays an important role in preparing students to become competent professionals in understanding and explaining life phenomena. Microscope literacy is an important aspect in deeply understanding the structure and function of organisms that are not visible to the naked eye. This community service program aims to increase microscope literacy for biology education students. Through training activities, students are provided with in-depth knowledge about the use of microscopes, sample preparation techniques, and interpretation of microscopic observation results. The targets of this activity are students of the Department of Biology Education, Faculty of Science, Engineering and Applied Sciences, Mandalika University of Education. The methods used are: preparation, training and practical demonstrations, interactive discussions, and monitoring and follow-up. The results of this activity show an increase in students' understanding regarding the use of microscopes, as well as an increase in their skills in operating microscopes to observe microscopic structures. Apart from that, participation in this program also provides a strong motivation for students to explore the field of biology in more depth. The conclusion of this program is that students' microscope literacy has increased, which is marked by increased understanding and skills of biology education students regarding microscopes.